Aspectos epidemiológicos, clínicos e de diagnóstico da infecção por Babesia canis, em cães atendidos em clínicas veterinárias, em Belo Horizonte - Gisele Spiewak (1992)
Epidemiological, clinical and diagnostic aspects of Babesia canis infection were investigated in 397 dogs at 4 veterinary stablishments, in Belo Horizonte, Minas Gerais. Brazil. Organisms were detected in I6 (4.0%) blood smears examinated and soroprevalence by indirect immunofluorescent antibody test was 34.1%. Blood smears were more effective in detecting parasitemy when prepared with capillary than with venous blood and also when examined the peripheral than the centre region. Dogs up to 2 years old were more frequently parasitemic and less frequently soropositive than the older ones. Dogs up to 6 months of age presented lower soroprevalence. No association was observed between sex or breed and parasitemy or soroprevalence. Association was observed between tick infestation and parasitemy, but not with soroprevalence. Parasitemy was more frequently detected in anoretic or letargic dogs or in those presenting vomit with bloody diarrhea. The highest soroprevalence was observed among r dogs with neoplasy or traumatism, and the lowest among dogs presentig vomit and bloody diarrhea. Soroprevalence among 5l street dogs was 78,4%.